Physician Specialty Choice under Uncertainty - Nicholson, Sean (Journal of Labor Economics, 2002)
Medical students must receive residency training in a specialty before they can practice medicine in the United States. Since the residents' salaries do not adjust across specialties, residency positions are rationed, and medical students face uncertainty when choosing a specialty. Using a data set with the preferred and realized specialties for 7,200 medical students, I estimate a model where students consider entry probabilities when selecting a specialty. I find that medical students are responsive to expected income differences between specialties, which implies that policies that increase the income of primary care physicians can address shortages in these specialties.